2018
DOI: 10.20885/jif.vol14.iss2.art1
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat kepatuhan pasien HIV/AIDS terhadap penggunaan obat anti retroviral (ARV) di RSUD Gunung Jati Cirebon

Abstract: Background: Acquired Immune Deficiency Syndrome (AIDS) is a syndrome or symptoms with severe immune deficiency as a late-stage manifestation. Antiretroviral (ARV) is a drug that can suppress the development of HIV in the body. Some ARVs commonly used in Indonesia include Lamivudin and Zidovudin. Adherence to antiretroviral treatment has been recognized as an essential component for achieving an optimal therapeutic program. Objective: This study aimed to determine the characteristics of patients, treatment char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Hanya saja terapi yang biasanya digunakan untuk menekan perkembangan virus dalam tubuh yaitu dengan menggunakan obat-obatan Antiretroviral (ARV) seperti Lamivudin dan Zidovudin yang harus dikonsumsi seumur hidup. [4] Akibat permasalahan kasus infeksi HIV ini mendorong kita untuk mencari solusi dan alternatif yang tepat untuk penanganannya. salah satunya dengan memanfaatkan sumber daya alam yang ada.…”
Section: Latar Belakangunclassified
“…Hanya saja terapi yang biasanya digunakan untuk menekan perkembangan virus dalam tubuh yaitu dengan menggunakan obat-obatan Antiretroviral (ARV) seperti Lamivudin dan Zidovudin yang harus dikonsumsi seumur hidup. [4] Akibat permasalahan kasus infeksi HIV ini mendorong kita untuk mencari solusi dan alternatif yang tepat untuk penanganannya. salah satunya dengan memanfaatkan sumber daya alam yang ada.…”
Section: Latar Belakangunclassified
“…Consumption of ARV must be according to the dose and time continuously erased because non-adherence to ARV or stopping ARV therapy can cause the body of PLHIV to experience resistance to ARV it can increase the risk of HIV / AIDS infection, as well as high mortality of PLHIV. Based on a study conducted by Hidayati et al (2018), it was found that the compliance rate of high ARV consumption was 44%, while as many as 34.7% were included in the moderate level category and as many as 21.3% in the low category (Hidayati et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed optimal compliance in Indonesia are still below 80%. [1][2][3] Thus resulted in increasing the incidence of intestinal protozoa infections, leading to faster AIDS development, drug resistance, and treatment failure. 4,5 Based on the Situation Report on the Development of HIV-AIDS in Indonesia, July -September 2016, DKI Jakarta Province ranked in the 5th province with the highest incidence of new HIV infections and AIDS so it requires health care facilities that are able to reach people who need HIV services and ARV therapy, both public or private health care facilities.…”
Section: Introductionmentioning
confidence: 99%